Teachers' lived experiences of responsible leadership: a transcendental phenomenological study - MacTaggart, Ryan, author; Lynham, Susan, advisor; Frederiksen, Heidi, advisor; Coke, Pamela, committee member; Hughes, Blanche, committee member (Colorado State University. Libraries, 2018)
Research regarding Responsible Leadership seems to be dispersed, making it difficult to understand the construct's place in leadership literature and the construct's role in theory and practice. There also seems to be a lack of the teacher voice in informing general school leadership and Responsible Leadership of schools. In response, this study intended to address Responsible Leadership from the perspective of middle school teachers. The purpose of the study was to construct a shared essence of five middle school teachers' lived experiences of the phenomenon of Responsible Leadership in order to inform theory and research of the construct as well as middle school leadership practice. This study was grounded in the constructivist paradigm to understand and analyze description of Responsible Leadership. Descriptive phenomenology served as the methodology. Data were collected and analyzed according to the processes of transcendental phenomenology with an additional use of mental models as tools for meaning making. The theory of Responsible Leadership for Performance (Lynham, 1998, 2000, 2002, 2004), constructed as a system of inputs, process and outputs, framed the study. The processes of the system in the theory were described as 3Es: effectiveness, ethics, and endurance. Thus, participants were asked to describe Responsible Leadership through each of the 3Es. The findings from this study represented the participants' shared descriptions of what they have experienced as Responsible Leadership and how they have experienced it in the context of middle schools in a western state of the United States. Shared textural descriptions of what participants experienced included Responsible Leadership as: diligence for physical presence and engagement in education; opening Responsible Leadership to more people through humility, listening, and building teams; a dedication to development for teachers and formal leadership; taking ownership of the leadership role; showing a genuine care for teachers as people and professionals; consistency in behavior and treatment; fortitude for tough situations; guidance from values and vision; and desirable outcomes for teachers. The shared structural descriptions of how participants experienced Responsible Leadership included: time in the profession, occupational background, leadership exposure, and leadership in formal positions. Additionally, the data were revisited to seek associations between participant descriptions and specifics of the 3Es to inform the Responsible Leadership for Performance theory. This three-pronged analysis led to a shared essence of Responsible Leadership from the lived experiences of the five participants. Ensuing recommendations are provided for theory, research, and practice. First, suggestions for research include: further inquiry into Responsible Leadership, honoring the value of the teacher perspective, constructing meaning through mental models, and understanding school leadership as a set of parallel systems. Second, implications for informing and refining theory are provided. Last, the practices of multiple stakeholders of the school leadership system are discussed including: state level leaders, formal school leaders, teachers, parents and community members, and those who develop future school leaders.
Keywords: phenomenology; school leadership; middle school; teachers; responsible leadership